Analysing english online resources for children: a practical case with an evaluation template proposal - Castillo Rodríguez, Cristina; Arias Montañana, Beatriz (Pixel-Bit. Revista de Medios y Educación, 2019)
Internet provides us, as teachers, with a wide range of tools and resources for practising English in an online environment. However, due to the vast amount of digital resources at our disposal today, and taking into account that not everything found on the net is reliable, we have no other option but to evaluate the resources. On the other hand, on the net we can find several already-created templates for analysing online resources. But, quite often, most of these templates include many indicators that will make the task of evaluating more time consuming, or do not include indicators for assessing the adequacy of the site as far as level, theme and linguistic skills of a foreign language, in our case, English, are concerned. The purpose of this paper is to propose a template enabling ESL or EFL teachers to gather suitable information per online resource and also to analyse some real sites in accordance with the parameters and indicators of the template.
Análisis de recursos online en inglés para niños: un caso práctico con una propuesta de plantilla de evaluación
Internet nos ofrece a los docentes una gran variedad de herramientas y recursos para practicar inglés en un entorno online. Sin embargo, debido a la gran cantidad de recursos digitales que están a nuestra disposición, y teniendo en cuenta que no todo lo que se encuentra en la red es fiable, no tenemos otra opción que evaluar nosotros mismos estos recursos. Por otro lado, en la red podemos encontrar plantillas creadas para analizar recursos online. Pero, a menudo, muchas de estas plantillas incluyen muchos indicadores que requieren mucho tiempo para su evaluación o bien no contemplan indicadores para evaluar la idoneidad del recurso en lo que respecta a nivel, temática y destrezas lingüísticas de una lengua extranjera, en nuestro caso, inglés. El objetivo de este artículo es proponer una plantilla que posibilite a los docentes de inglés como segunda lengua/lengua extranjera reunir suficiente información de cada recurso digital y analizar también algunos recursos reales de acuerdo con los parámetros e indicadores propuestos en la plantilla
Keywords: english; information sources; information technology; foreign languages; online searching; inglés; fuente de información; tecnología de la información; lengua extranjera; búsqueda en línea; Emerging; Scopus